Analisis Spasial Kenaikan Cooling Degree Days dan Estimasi Beban Energi Pendingin Ruang Kelas di Kota Medan Berbasis Data Nasa Power dan Statistik Pendidikan BPS - Aidil Akbar Bagaskara (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2026)
Urban climate change and rapid urbanization in Medan City have the potential to increase the demand for space-cooling energy, including in primary education facilities. This study examines indications of increasing Cooling Degree Days (CDD) in Medan City based on the NASA POWER satellite meteorological data framework and estimates exposure to cooling-energy loads in elementary school classrooms across 21 districts using official data from the Center for Data and Information Technology (Pusdatin) of the Ministry of Primary and Secondary Education and the Central Statistics Agency (BPS) of Medan City. The approach used is descriptive-quantitative with a hazard-exposure framework, considering that the spatial resolution of NASA POWER data, approximately 0.5° × 0.625° or equivalent to 55–60 km, is coarser than the administrative area of Medan City, which covers 265.10 km². As a result, the spatial variation of CDD is relatively homogeneous at the city level, while exposure variation, represented by the number and density of classrooms, differs significantly among districts. The results show that Medan Marelan District, with 28 elementary schools and an estimated 168 classrooms; Medan Denai, with 24 elementary schools and 144 classrooms; as well as Medan Belawan, Medan Deli, and Medan Labuhan, each with 21 elementary schools and 126 classrooms, have the highest exposure to cooling-energy loads if the citywide CDD trend continues to increase. In contrast, Medan Polonia, with 4 elementary schools, and Medan Baru and Medan Barat, each with 5 elementary schools, have the lowest exposure. This study recommends the integration of higher-resolution data, such as BMKG station data or finer-resolution satellite imagery, in future research, as well as prioritizing cooling-energy efficiency interventions in districts with the highest classroom density.